Dental conditions in inpatients with schizophrenia: A large-scale multi-site survey - Tani Hideaki; Uchida Hiroyuki; Suzuki Takefumi; Shibuya Yumi; Shimanuki Hiroshi; Watanabe Koichiro; Den Ryosuke; Nishimoto Masahiko; Hirano Jinichi; Takeuchi Hiroyoshi; Nio Shintaro; Nakajima Shinichiro; et al. (BMC, 2012)
Abstract Background Clinical relevance of dental caries is often underestimated in patients with schizophrenia. The objective of this study was to examine dental caries and to identify clinical and demographic variables associated with poor dental condition in patients with schizophrenia. Methods Inpatients with schizophrenia received a visual oral examination of their dental caries, using the decayed-missing-filled teeth (DMFT) index. This study was conducted in multiple sites in Japan, between October and December, 2010. A univariate general linear model was used to examine the effects of the following variables on the DMFT score: age, sex, smoking status, daily intake of sweets, dry mouth, frequency of daily tooth brushing, tremor, the Clinical Global Impression-Schizophrenia Overall severity score, and the Cumulative Illness Rating Scale for Geriatrics score. Results 523 patients were included in this study (mean ± SD age = 55.6 ± 13.4 years; 297 men). A univariate general linear model showed significant effects of age group, smoking, frequency of daily tooth brushing, and tremor (all p's < 0.001) on the DMFT score (Corrected Model: F(23, 483) = 3.55, p < 0.001, R2 = 0.42) . In other words, older age, smoking, tremor burden, and less frequent tooth brushing were associated with a greater DMFT score. Conclusions Given that poor dental condition has been related with an increased risk of physical co-morbidities, physicians should be aware of patients' dental status, especially for aged smoking patients with schizophrenia. Furthermore, for schizophrenia patients who do not regularly brush their teeth or who exhibit tremor, it may be advisable for caregivers to encourage and help them to perform tooth brushing more frequently.